Development of elite sportsmen`s training system - Yessentayev, T. K. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to study conditions and organizational management forms of material-technical and personnel potential`s realization in modern system of elite sportsmen`s training. Material: publications on the topic of the article were used as sources of information. Results: approaches to optimization of sportsmen`s training and competition functioning management were analyzed. In the basis of modern system of elite sportsmen`s training for competition functioning is realization of knowledge and practical experience of different specialists. Provisioning of conditions for different profiles specialists` participation in sportsmen`s training is ensured by large training centers with developed infrastructure and wide complex of services for sportsmen. Conclusions: coordination of different profiles` specialists in sportsmen`s preparation for competition functioning and in competition functioning is ensured by different forms of management. The most effective of them is model of chief coach`s and chief of complex scientific group`s cooperation.